Implementasi Jaminan Produk Halal Menurut Undang-Undang Nomor 33 Tahun 2014 (Studi Kasus Pada KUA Kecamatan Setu Kabupaten Bekasi) - Irawan, Anggi; Fauziah, Fauziah (Konsorsium Dosen Sekolah Tinggi Agama Islam (STAI) Al-Yasini Pasuruan, 2024)
This paper aims to determine the implications of halal certification for the halal product business especially in Setu District, Bekasi Regency. The issue of halal has become a global trend marked by the presence of halal certification institutions in various parts of the world. As a form of government attention, a law on guaranteeing halal products was made as a legal umbrella to provide protection to consumers, especially Muslim consumers. The birth of Law Number 33 of 2014 concerning Halal Product Guarantee actually emphasizes the urgency of the halalharam issue in the production chain from business actors to consumers and is consumed by consumers, where there is also a role for intermediaries such as distributors, sub-distributors. wholesalers, and retailers before it reaches the final consumer. This paper uses descriptive qualitative methods through a review of relevant literature and observations of the practice of implementing halal guarantee systems in Indonesia. Data obtained through journals, books, magazines, newspapers, electronic media, such as the official website of LPPOM MUI and personal communication with competent sources. The results showed that the certification of halal products has positive implications in building a halal business climate in Indonesia. For consumers, halal certification provides protection, guarantees, product halal information and becomes an instrument of business ethics. For business people, halal certification provides benefits to increase consumer confidence.